saifoal7elo
saifoal7elo
04-09-2020
SAT
contestada
If f(x)=x+1 and g(x)= 3x+4 then f(g(2)) - g(f(2))=
Respuesta :
amoleh25
amoleh25
05-09-2020
g(2) = 3(2) + 4
g(2) = 10
f(2) = (2) + 1 = 3
g(3) = 3(3) + 4 = 13
f(10) = (10) + 1 = 11
11 - 13 = -2
Final Answer: -2
Answer Link
VER TODAS LAS RESPUESTAS ( 97+ )
Otras preguntas
Please help!!!! URGENT!!!!!!!!!!!!!!!!!!!!!
The_____ form acidic compounds with hydrogen.
help me asap !!!!!!!!
What is the solution to the following equation? 5(2x − 14) + 23 = 7x − 14 11 14 30 36
The length of the shorter base in an isosceles trapezoid is 4 in, its altitude is 5 in, and the measure of one of its obtuse angles is 135°. Find the area of th
What is true concerning an ecological community? it is a large region of multiple organisms the boundaries, large or small, of a single organism the ecosystem o
How many meters are there in 21 feet?
why are the hindlimbs important on the frog
The_____ form acidic compounds with hydrogen.
PLSSSSSS HELP 30PTSSSSSS!!!!!!!!!!!!!